Follicular helper T cell in immunity and autoimmunity - Mesquita Jr,D. (2016)
The traditional concept that effector T helper (Th) responses are mediated by Th1/Th2 cell subtypes has been broadened by the recent demonstration of two new effector T helper cells, the IL-17 producing cells (Th17) and the follicular helper T cells (Tfh). These new subsets have many features in common, such as the ability to produce IL-21 and to express the IL-23 receptor (IL23R), the inducible co-stimulatory molecule ICOS, and the transcription factor c-Maf, all of them essential for expansion and establishment of the final pool of both subsets. Tfh cells differ from Th17 by their ability to home to B cell areas in secondary lymphoid tissue through interactions mediated by the chemokine receptor CXCR5 and its ligand CXCL13. These CXCR5+ CD4+ T cells are considered an effector T cell type specialized in B cell help, with a transcriptional profile distinct from Th1 and Th2 cells. The role of Tfh cells and its primary product, IL-21, on B-cell activation and differentiation is essential for humoral immunity against infectious agents. However, when deregulated, Tfh cells could represent an important mechanism contributing to exacerbated humoral response and autoantibody production in autoimmune diseases. This review highlights the importance of Tfh cells by focusing on their biology and differentiation processes in the context of normal immune response to infectious microorganisms and their role in the pathogenesis of autoimmune diseases.